2017
DOI: 10.1177/1076029617741362
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Monocyte to High-Density Lipoprotein Cholesterol Ratio in the Presence and Severity of Metabolic Syndrome

Abstract: Monocyte to high-density lipoprotein cholesterol ratio (MHR) is a systemic inflammatory marker, and recently, it has been used quite commonly for the assessment of inflammation in cardiovascular disorders. The aim of the present study is to investigate the relevance of MHR as a marker to assess metabolic syndrome (MetS) and MetS severity in clinical practice. A total of 147 patients with MetS who were diagnosed according to National Cholesterol Education Program Adult Treatment Panel III criteria and 134 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…MHR as the combination of both monocytes and HDL-C has been proposed as a novel inflammatory index [20]. Recent clinical and epidemiological studies have established that MHR has the ability to predict multiple inflammation-related diseases, such as metabolic syndrome, diabetes mellitus, atrial fibrillation and coronary artery disease [21][22][23][24]. Recent researches have revealed the significant association between inflammation and elevated uric acid level [2,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MHR as the combination of both monocytes and HDL-C has been proposed as a novel inflammatory index [20]. Recent clinical and epidemiological studies have established that MHR has the ability to predict multiple inflammation-related diseases, such as metabolic syndrome, diabetes mellitus, atrial fibrillation and coronary artery disease [21][22][23][24]. Recent researches have revealed the significant association between inflammation and elevated uric acid level [2,9].…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte-to-HDL-C ratio (MHR) has been proposed as a potentially modifiable marker of inflammation [20]. Additionally, previous studies have found that MHR has the capacity to predict a variety of inflammation-related diseases [21][22][23][24]. As yet, no study has been conducted on the potential association between MHR and the prevalent hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, leukocytes' subtypes have been considered useful systemic inflammation markers [6] as well as neutrophil-to-lymphocyte ratio (NLR) [7,8], platelet-to-lymphocyte ratio (PLR) [9,10], lymphocyte-to-monocyte ratio (LMR) [11,12]and monocyte-to-HDL ratio (MHR) [13][14][15][16][17][18] indexes. Furthermore, several studies underlined the link between NLR, PLR, LMR, MHR and cardiovascular diseases, like peripheral arterial occlusive disease, coronary artery diseases (including myocardial infarction), atrial fibrillation and aortic alterations but the association with MS is still not well established [12,16,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Then monocytes differentiate into macrophages and these macrophages start to phagocytes of oxidized LDL and become foam cells [15,16]. Previous studies have been associated with the severity of coronary artery disease and low LMR and high MHR has been regarded as a surrogate marker for endothelial dysfunction and inflammation [17,18]. In this study, first time in the literature, drug naïve MetS patient's value of the LMR and MHR were compared the healthy age and BMI matched ones.…”
Section: Discussionmentioning
confidence: 98%